Human Vδ2+ γδ T cells differentially induce maturation, cytokine production and alloreactive T cell stimulation by dendritic cells and B cells - Petrasca, Andreea; Doherty, Derek G. (Frontiers in Immunology, 2014)
Human γδ T cells expressing the Vγ9Vδ2 T cell receptor can induce maturation of dendritic (DC) into antigen-presenting cells (APC) and B cells into antibody-secreting plasma cells. Since B cells are capable of presenting antigens to T cells, we investigated if Vγ9Vδ2 T cells can influence antigen presentation by these cells. We report that Vδ2 T cells induced expression of CD86, HLA-DR and CD40 by B cells and stimulated the release of IL-4, IL-6, TNF-α, and IgG, IgA and IgM. Vγ9Vδ2 T cells also augmented the ability of B cells to stimulate proliferation but not IFN-γ or IL-4 release by alloreactive T cells. In contrast, Vγ9Vδ2 T cells induced expression of CD86 and HLA-DR and the release of IFN-γ, IL-6 and TNF-α by DC and these DC stimulated proliferation and IFN-γ production by conventional T cells. Furthermore, CD86, TNF-α, IFN-γ and cell contact were found to be important in DC activation by Vγ9Vδ2 T cells but not in the activation of B cells. These data suggest that Vγ9Vδ2 T cells can induce maturation of B cells and DC into APC, but while they prime DC to stimulate T helper 1 (TH1) responses, they drive maturation of B cells into APC that can stimulate different T cell responses. Thus, Vγ9Vδ2 T cells can control different arms of the immune system through selective activation of B cells and DC in vitro, which may have important applications in immunotherapy and for vaccine adjuvants.